POSTOPERATIVE SORE THROAT AFTER ELECTIVE SURGICAL PROCEDURES - Ahmed, Aliya; Abbasi, Shemaila; Ghafoor, Hasham Bin; Ishaq, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Postoperative sore throat is a common complication of anaesthesia and can lead to dissatisfaction after surgery. Many factors can contribute to postoperative sore throat and the incidence varies with the method of airway management Methods: In this prospective observational study elective gynaecological and general surgical patients were interviewed 24 hours postoperatively to determine the presence of sore throat. Information collected included demographic data, surgical procedure, duration of surgery, airway device used and position of patient during surgery. This study was done over a period of 3 months. Results: 312 patients were interviewed. 81(26%) patients suffered with sore throat postoperatively. 28% of patients with endotracheal intubation (ETT) and 3.5% of patients with laryngeal mask airway had a sore throat. Female patients reported more sore throat than male patients (27.1% vs. 19.1%). Sore throat was found to be more common with older age group, grade of difficulty in intubation, duration of surgery and patient's position during surgery. Conclusion: Awareness of the factors responsible for increased incidence of postoperative sore throat and appropriate care especially during endotracheal intubation can help to reduce the incidence of postoperative sore throat. Keywords: Anaesthetic complications; Postoperative; Sore throat